Respuesta :

For this case we have that a quadratic equation is of the form:[tex]ax ^ 2 + bx + c = 0[/tex]

Where:

a: is the main coefficient because it accompanies the quadratic variable.

b: It is the linear coefficient

c: It is the constant term.

Then, a quadratic function with a main coefficient of "3" and a constant term of "-12" is:

[tex]f (x) = 3x ^ 2 + 11x-12[/tex]

Answer:

Option B

[tex]f (x) = 3x ^ 2 + 11x-12[/tex]

Answer:

It is B. f(x) = 3x2 + 11x – 12

Step-by-step explanation:

If this question is on Edg, then it is B, & B is Correct.